Experimental Study on the Mechanical Behavior of Orthodontic Arches Exposed to the Environment in the Oral Cavity - Alexandru Stefan Zalana; Maria Dămășaru; Edgar Moraru; Ciprian Ion Rizescu; Simina Neagoe (Chelărescu); Mariana Păcurar (MDPI AG, 2022)
Background. The arches used in orthodontic therapy are subject to increasing physical and chemical stresses. Purpose of the study: This in vitro experimental study aims to highlight and compare the main mechanical properties of orthodontic arches. Materials and Methods: We used 40 springs, 2 materials, 20 of Ni-Cr and 20 of Co-Cr, of different diameters, 0.7 mm 0.8 mm and 1.2 mm, subjected to the environment of artificial saliva and artificial saliva with cola for one month and two months, respectively. Five springs of each material were tested at different times: T0, before application in the oral cavity, then at time T1, T2, T3, T4. Three lengths of the lever arm were considered for bending forces acting on the springs (dental wires). These lengths were 15, 10 and 5 mm. The wires were tested under the action of bending forces on a Hans Schmidt HV 500N stand, obtaining the characteristics of the wires: deformation-force-time. Results: Graphical determinations show that the degree of deformation of the wires is influenced by the applied force, diameter and obviously by the immersion time, respectively by the type of solution in which the springs were immersed. Conclusions: The final degree of bending is higher for Co-Cr arcs than for Ni-Cr at all three dimensions.